Association Between Ultra-Processed Food Consumption and Cognitive Performance Among Adolescent Students From Underdeveloped Cities in Brazil: A Cross-Sectional Study - João Victor Laurindo dos Santos; João Victor Laurindo dos Santos; Ingrid Sofia Vieira de Melo; Clara Andrezza Crisóstomo Bezerra Costa; Clara Andrezza Crisóstomo Bezerra Costa; Layanne Cabral de Almeida; Dafiny Rodrigues Silva; Débora Cavalcante Ferro; Déborah Tenório Costa Paula; Mateus de Lima Macena; Nassib Bezerra Bueno; Nassib Bezerra Bueno (Frontiers Media S.A., 2024)
ObjectivesThe association between ultra-processed foods (UPF) consumption and cognitive performance needs to be better characterized in adolescents, especially in low-income settings, where the cost of human capital is high. This study investigated the association between cognitive performance and UPF in adolescents from the countryside of the Brazilian Northeast.MethodsAdolescents (15-18 years old) from three public high schools were included. Food intake was assessed using three 24-hour dietary recalls. The classification of foods as UPF was determined according to the Nova classification. Cognitive performance was evaluated using the Non-Verbal General Intelligence Test.Results116 adolescents were included, of which 50 (43.1%) showed low cognitive performance. The average energy intake was 1973.5 kcal, with 24.2% coming from UPF. Participants with low cognitive performance consumed 26.5% (95% CI: [22.2; 30.7]%) of daily energy intake from UPF compared to 22.5% ([18.8; 26.2]%) of those with medium-high cognitive performance (P = 0.17), without differences in energy and macronutrient intake.ConclusionDespite similar UPF consumption compared to the Brazilian average, no association was found between UPF consumption and cognitive performance in this low-income adolescent sample.